Maquinado y susceptibilidad a la impregnación de la madera del hule (Hevea brasiliensis) - Ordóñez Candelaria, Victor Rubén; Martínez Castillo, José Luis (Instituto de Ecología, A.C., 2016)
A research work on machining and treatability was carried out with a sample of rubber wood from a plantation in the state of Veracruz, in order to increase the level of technological information on those subjects. The results of the study define the machining characteristics according to ASTM Standards. Taking these results as a basis (regular for most processes), required modifications to the machining process can be acomplished in order to improve the finishing in those cases in which it is required. The rubber wood is considered to be permeable.